How Did the Translation of Genovefa by Christoph von Schmidt Become the 19th-Century Lithuanian Vestseller? - Navickienė, Aušra (Knygotyra, 2022)
This article analyses the repertoire of nineteenth-century Lithuanian fiction to identify cases of bestsellers and to reconstruct their publishing history. The concept of nineteenth-century Lithuanian fiction publication is broadly understood. It includes fiction printed in the Lithuanian language in Lithuania, Lithuania Minor and the Lithuanian emigration from 1795, when the third partition of Poland and Lithuania took place and the lands of the Grand Duchy of Lithuania were annexed by Russian empire, until 1904, when the ban on printing in Latin script, which lasted for four decades after 1864, was lifted. The history of the translation and publication of German writer Christoph von Schmidt’s work Genovefa was selected as a study case. A study was conducted to find answers to various issues: Does this publication with its fifteenth editions qualify as the Lithuanian bestseller? What factors led to the large number of new editions of this title? How did contrafactions (publications with intentionally false imprints) contribute to book sales during the ban on publishing in Latin characters in Lithuania? The research findings reveal publishing trends characteristic of Europe in a phase of modernisation (new business models of the publishing industry, growing public literacy and changing public demand for reading material). In addition, they show the peculiarities of nineteenth-century book publishing and the book trade in the European regions involved in a struggle against occupation and for the preservation of their national identities.